Formation, thermal redox reaction and crystal structure of δ-CaCr2O4 - Kim, Jaegyeom; Shin, Jinho; Paek, Seung Min; Park, Dae Sung; Kim, Seung Joo (Journal of Solid State Chemistry, 2022)
The thermal redox reactions of a Ca–Cr–O system under different atmospheric conditions were investigated by cyclic thermodiffractometry and thermogravimetry. In the first heating process under a reductive atmosphere, CaCrO4 decomposed into CaO and δ-CaCr2O4, a metastable form, with the liberation of free oxygen. In the second process under an oxidizing atmosphere, the CaO and δ-CaCr2O4 produced in the first reduction process reacted to regenerate CaCrO4, indicating that this redox reaction could proceed reversibly upon controlling the atmosphere. The crystal structure of δ-CaCr2O4 was determined, for the first time, on the basis of high-resolution synchrotron powder X-ray diffraction data. δ-CaCr2O4 crystallized in a monoclinic structure with the space group P21/m. The structure can be described as a stacking of CrO2 layers composed of edge-sharing CrO6 octahedra, with calcium ions residing on-site between the layers. The calcium ions were coordinated by six oxygen atoms to form a trigonal prism geometry between the CrO2 layers. The structure of δ-CaCr2O4 was different from those of low-temperature β-CaCr2O4 (distorted CaFe2O4-type) and high-temperature α-CaCr2O4 (P2-type layered structure).
Keywords: Atmospheric conditions; Calcium chromite; Calcium ions; Crystal structure determination; Crystals structures; Reaction structures; Reversible thermal redox reaction; Thermal; Thermodiffractometry; Δ-cacr2O4; Calcium chromite; Crystal structure determination; Polymorphism; Reversible thermal redox reaction; δ-CaCr2O4